Optimization of the Unit I Performance to Uncover Criminal Acts of Theft in the Jurisdiction of the Pati City Resort Police - Putra, I Kadek Agus Dana (Advances in Police Science Research Journal, 2024)
The purpose of this study is to optimize the ability of members of the General Crime Unit I Satreskrim Polresta Pati in disclosing criminal acts of theft by weighting. Improving the management of General Crime Unit I Satreskrim Polresta Pati in disclosing criminal acts of theft by weighting. The theory used is management theory and Swot analysis theory while the concepts used are the concept of investigation and investigation and the concept of weighted theft. This research method is the method of field studies or field research, namely by conducting research directly to the field or the location of the research object. The research location is in the jurisdiction of Polresta Pati which is located at Jalan A. Yani Number 1, Ngarus, Pati District, Pati Regency, Central Java Province which has the postal code 59112 according to the Order of the Governor of the Police Academy Number: SPRIN/618/VIII/DIK. 2.6/2022 concerning Implementation of Internships for Police Academy Cadets. The results of this study show that the General Crime Unit I's ability to disclose criminal acts of theft by weighting in the jurisdiction of the Pati Police is still not optimal. This is influenced by several factors analyzed using the SWOT theory, namely the number of personnel who are not optimized properly, the opportunities they have are not properly utilized, the lack of quality possessed by personnel, the limited facilities and infrastructure to support activities, and the growing mode of theft perpetrators. with weighting. As well as the system and methods used in disclosing criminal acts of theft by weighting have not been implemented optimally. This is due to the fact that good activity planning has not been established, the coordination system is lacking, the implementation often experiences problems, and the lack of oversight of the performance of the General Crimes Unit I.